Biomedical application of chitosan-based nanoscale delivery systems: Potential usefulness in siRNA delivery for cancer therapy - Ashrafizadeh, Milad; Delfi, Masoud; Hashemi, Farid; Zabolian, Amirhossein; Saleki, Hossein; Bagherian, Morteza; Azami, Negar; Farahani, Mahdi Vasheghani; Sharifzadeh, Seyed Omid; Hamzehlou, Soodeh; Hushmandi, Kiavash; Makvandi, Pooyan; et al. (Carbohydrate polymers, 2021)
Gene therapy is an emerging and promising strategy in cancer therapy where small interfering RNA (siRNA) system has been deployed for down-regulation of targeted gene and subsequent inhibition in cancer progression; some issues with siRNA, however, linger namely, its off-targeting property and degradation by enzymes. Nanoparticles can be applied for the encapsulation of siRNA thus enhancing its efficacy in gene silencing where chitosan (CS), a linear alkaline polysaccharide derived from chitin, with superb properties such as biodegradability, biocompatibility, stability and solubility, can play a vital role. Herein, the potential of CS nanoparticles has been discussed for the delivery of siRNA in cancer therapy; proliferation, metastasis and chemoresistance are suppressed by siRNA-loaded CS nanoparticles, especially the usage of pH-sensitive CS nanoparticles. CS nanoparticles can provide a platform for the co-delivery of siRNA and anti-tumor agents with their enhanced stability via chemical modifications. As pre-clinical experiments are in agreement with potential of CS-based nanoparticles for siRNA delivery, and these carriers possess biocompatibiliy and are safe, further studies can focus on evaluating their utilization in cancer patients.
Keywords: Small interfering RNA (siRNA); Drug Resistance, Neoplasm; Neoplasms; Nanoparticles; nádory; umlčování genů; Drug Carriers; Gene Silencing; lidé; chitosan; Antineoplastic Agents; protinádorové látky; chemorezistence; malá interferující RNA; Chitosan; Nanoparticle; nanočástice; RNA, Small Interfering; Cancer therapy; nosiče léků; Gene delivery; Humans